(untitled) (Revista Innova Educación, 2024)
In this study, we aimed to evaluate the effectiveness of an enhanced Education 4.0 proposal incorporating Service Learning (SL) among university students. A quantitative research was conducted with a sample of 30 students from Universidad de Aconcagua (Chile) during the period from April to June 2024. Data were collected using questionnaires with sufficient validity and reliability; the first instrument assessed Grit on the 12-item Grit-O scale with scores ranging from 1 to 5, with 5 being the highest level, and the second instrument measured social responsibility from 1 to 6, with 6 as the maximum value. The results indicate that the use of Education 4.0 along with Service Learning showed a significant increase in social responsibility, rising from 4.96 to 5.37 (p<0.05), and a slight increase in Grit, from 4.36 to 4.41, achieving better outcomes than students who only used Education 4.0. The findings suggest that Education 4.0 with Service Learning projects is a more effective methodology than Education 4.0 alone for increasing Grit and social responsibility among university students.